Isotope effect in transient electron thermal transport property and its impact on the electron internal transport barrier formation in LHD. (15th June 2020) - Kobayashi, T.; Ida, K.; Tanaka, K.; Yoshinuma, M.; Tsujimura, T.Ii; Inagaki, S.; Tokuzawa, T.; Tsuchiya, H.; Tamura, N.; Igami, H.; Yoshimura, Y.; Itoh, S.-I.; et al.
Abstract: In this study, we perform a comprehensive comparison of the transport hysteresis width in deuterium (D) plasmas, hydrogen (H) plasmas, and D-H mixed plasmas. The core focused modulation electron cyclotron resonance heating (MECH) is applied as the heat source perturbation, and the heat flux is evaluated using the energy conservation equation with the measured electron temperature response and the ECH deposition profile calculated by the ray-tracing scheme. Systematic density scan in plasmas with different ion mass reveals that there is no significant isotope effect in their hysteresis width. It is found that plasmas with heavier isotope mass can easily form the electron internal transport barrier. As the hysteresis width is insensitive to the isotope mass, the classical part of the diffusivity is considered to be responsible for the isotope effect in the transport barrier formation.